Proposed narrowband biphoton generation from an ensemble of solid-state quantum emitters - Jeong, Heejeong; Du, Shengwang; Kim, Na Young (Optical Society of America, 2019)
We explore a mechanism for producing time-frequency entangled photon pairs (termed a biphoton) from an ensemble of atom-like solid-state quantum emitters. Four distinct energy levels of the solid-state system render four spin-conserving optical transitions as observed in color centers. This feature opens up the possibility to generate a four-wave mixing biphoton based on an electromagnetic induced transparency (EIT) for long-coherence quantum communication as demonstrated in cold atomic systems. We propose a narrow EIT window below a lifetime-limited linewidth of a SiV− in diamond, assuming a few hundred MHz. Consequently, the EIT-induced narrowband guarantees biphoton coherence time to be at least a few tens of a nanosecond without a cavity. Assessing the criteria of solid-state parameters applicable to the existing biphoton model from cold atoms will accelerate solid-state biphoton source research. This study shows that a realization of negligible ground state dephasing of a solid-state sample will be a crucial step toward a solid-state biphoton generation for more than a 100 ns time scale with a subnatural atomic linewidth of a few MHz. © 2019 Optical Society of America.